2019
DOI: 10.1002/mgg3.993
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of alpinetin on IL‐6 expression by promoting cytosine methylation in CpG islands in the IL‐6 promoter region

Abstract: Background: Alpinetin is a flavonoid which exerts antibacterial and anti-inflammatory functions. In order to prove that the induced methylation is an important mechanism for alpinetin in regulating the expression of inflammatory factor Interleukin-6 (IL-6), we detected the dinucleotide methylation status of CpG islands in the IL-6 promoter region and IL-6 level after treatment of RAW246.7 murine macrophages with alpinetin. Methods: After RAW246.7 murine macrophages were treated with alpinetin, alpinetin + GW96… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Moreover, Hu et al calculated that alpinetin administration (50-1,000 μg/ml for 24 h) apparently activated PPAR and reduced proinflammatory cytokines IL-6 generation in RAW246.7 cells. The mechanism analysis clarified that alpinetin firstly enabled PPAR, whereafter activated DNMT3A and boosted cytimidine methylation of the IL-6 promoter region, and finally reduced IL-6 secretion (Hu et al, 2020).…”
Section: Activation Of Ppar-γmentioning
confidence: 96%
“…Moreover, Hu et al calculated that alpinetin administration (50-1,000 μg/ml for 24 h) apparently activated PPAR and reduced proinflammatory cytokines IL-6 generation in RAW246.7 cells. The mechanism analysis clarified that alpinetin firstly enabled PPAR, whereafter activated DNMT3A and boosted cytimidine methylation of the IL-6 promoter region, and finally reduced IL-6 secretion (Hu et al, 2020).…”
Section: Activation Of Ppar-γmentioning
confidence: 96%
“…Therefore, the PPAR/DNMT3A pathway is considered the main molecular mechanism involved in reversing inflammatory organ damage by alpinetin. 14 , 15 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we found that PPAR activation induced by alpinetin can further promote the synthesis and modification activity of DNA methyltransferase DNMT3A in the nucleus of RAW 246.7 (the macrophage cell line), thus promoting the methylated modification of the IL‐6 promoter and blocked the binding of transcription factors. Therefore, the PPAR/DNMT3A pathway is considered the main molecular mechanism involved in reversing inflammatory organ damage by alpinetin 14,15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNMT3A, as a major CpG methyltransferase, consists of an N-terminal binding domain and a C-terminal with transmethylation activity [ 21 ], regulating the target genes expression by quickly converting cytosine into 5-methylcytosine [ 22 ]. Galangin was found to promote the methylation of promoter CpG sites of IL-6, a key inflammatory gene, via the PPAR/DNMT3A pathway, thereby inhibiting IL-6 expression [ 23 ]. In summary, methylation induction should be part of the mechanism, wherein galangin intervenes to synthesize inflammatory mediators.…”
Section: Introductionmentioning
confidence: 99%